Plasma phospholipid dysregulation in patients with cystathionine-β synthase deficiency - Di Minno, Alessandro; Anesi, Andrea; Chiesa, Mattia; Cirillo, Ferdinando; Colombo, Gualtiero I.; Orsini, Roberta C.; Capasso, Filomena; Morisco, Filomena; Fiorelli, Susanna; Eligini, Sonia; Cavalca, Viviana; Tremoli, Elena; et al. (Nutrition, metabolism, and cardiovascular diseases, 2020)
Patients with cystathionine β-synthase deficiency (CBSD) exhibit high circulating levels of homocysteine and enhanced lipid peroxidation. We have characterized the plasma lipidome in CBSD patients and related lipid abnormalities with reactions underlying enhanced homocysteine levels. Using an ultra-high-performance liquid chromatography-electrospray ionization-quadrupole-time of flight-mass spectrometry method, plasma lipids were determined with an untargeted lipidomics approach in 11 CBSD patients and 11 matched healthy subjects (CTRL). Compared to CTRL, CBSD patients had a higher medium and long-chain polyunsaturated fatty acids (PUFA) content in phosphatidylethanolamine (PE) and lysophosphatidylethanolamine (LPE) species (p < 0.02), and depletion of phosphatidylcholine (PC; p = 0.02) and of lysophosphatidylcholine (LPC; p = 0.003) species containing docosahexaenoic acid (DHA), suggesting impaired phosphatidylethanolamine-N-methyltransferase (PEMT) activity. PEMT converts PE into PC using methyl group by S-adenosylmethionine (SAM) thus converted in S-adenosylhomocysteine (SAH). Whole blood SAM and SAH concentrations by liquid chromatography tandem mass spectrometry were 1.4-fold (p = 0.015) and 5.3-fold (p = 0.003) higher in CBSD patients than in CTRL. A positive correlation between SAM/SAH and PC/PE ratios (r = 0.520; p = 0.019) was found. A novel biochemical abnormality in CBSD patients consisting in depletion of PC and LPC species containing DHA and accumulation of PUFA in PE and LPE species is revealed by this lipidomic approach. Changes in plasma SAM and SAH concentrations are associated with such phospholipid dysregulation. Given the key role of DHA in thrombosis prevention, depletion of PC species containing DHA in CBSD patients provides a new direction to understand the poor cardiovascular outcome of patients with homocystinuria. [Display omitted] •CBSD patients have lower PC containing DHA and higher PE compared to controls.•CBSD patients have impaired phosphatidylethanolamine-N-methyltransferase activity.•CBSD patients exhibit a higher SAM/SAH ratio compared to controls.•Patients with steatosis have lower PC/PE ratio compared to those without.